Developmental atlas of the indirect-developing sea urchin Paracentrotus lividus: From fertilization to juvenile stages - Formery, Laurent; Wakefield, Axel; Gesson, Maeva; Toisoul, Ludovic; Lhomond, Guy; Gilletta, Laurent; Lasbleiz, Régis; Schubert, Michael; Croce, Jenifer C. (Frontiers in Cell and Developmental Biology, 2022)
The sea urchin Paracentrotus lividus has been used as a model system in biology for more than a century. Over the past decades, it has been at the center of a number of studies in cell, developmental, ecological, toxicological, evolutionary, and aquaculture research. Due to this previous work, a significant amount of information is already available on the development of this species. However, this information is fragmented and rather incomplete. Here, we propose a comprehensive developmental atlas for this sea urchin species, describing its ontogeny from fertilization to juvenile stages. Our staging scheme includes three periods divided into 33 stages, plus 15 independent stages focused on the development of the coeloms and the adult rudiment. For each stage, we provide a thorough description based on observations made on live specimens using light microscopy, and when needed on fixed specimens using confocal microscopy. Our descriptions include, for each stage, the main anatomical characteristics related, for instance, to cell division, tissue morphogenesis, and/or organogenesis. Altogether, this work is the first of its kind providing, in a single study, a comprehensive description of the development of P. lividus embryos, larvae, and juveniles, including details on skeletogenesis, ciliogenesis, myogenesis, coelomogenesis, and formation of the adult rudiment, as well as on the process of metamorphosis in live specimens. Given the renewed interest for the use of sea urchins in ecotoxicological, developmental, and evolutionary studies as well as in using marine invertebrates as alternative model systems for biomedical investigations, this study will greatly benefit the scientific community and will serve as a reference for specialists and non-specialists interested in studying sea urchins.